2016
DOI: 10.7860/jcdr/2016/21365.8726
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Immune Thrombocytopenic Purpura Secondary to Pulmonary Tuberculosis

Abstract: A 27-year-old, non-smoker male was admitted to the in-patient Department of Medicine of MKCG Medical College with complaints of intermittent fever not associated with chills and rigor for 8 days, shortness of breath {Medical Research Council (MRC) dyspnoea grade 2}, multiple purpuric spots over chest and extremities, epistaxis, bleeding per rectum, sub-conjunctival bleed and haematuria. There was no history of any haematological disorder, liver disease, cardiovascular disease or any medication intake in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The prevalence of thrombocytopenia among PTB patients was 20.00% while it was 14.29% among PTB/HIV coinfected patients. Different mechanisms such as immune mechanisms, bone marrow fibrosis, direct megakaryocyte infection, and hypersplenism had been implicated as possible causal factors for thrombocytopenia in PTB/HIV co-infected patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thrombocytopenia among PTB patients was 20.00% while it was 14.29% among PTB/HIV coinfected patients. Different mechanisms such as immune mechanisms, bone marrow fibrosis, direct megakaryocyte infection, and hypersplenism had been implicated as possible causal factors for thrombocytopenia in PTB/HIV co-infected patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…ITP is further differentiated into primary ITP or secondary ITP (6). Common secondary causes of ITP include autoimmune diseases like SLE, infections (HIV/hepatitis C), drugs (rifampicin), and lymphoproliferative disorders but tuberculosis per se is a very rare condition (8).…”
Section: Discussionmentioning
confidence: 99%
“…Weber et al concluded that early diagnosis and initiation of treatment for tuberculosis should be given the highest priority to reduce the use of immunosuppressants, transfusion, and the risk of hemorrhage [ 1 ]. There are 4 new case reports of ITP due to tuberculosis after Weber's report [ [4] , [5] , [6] , [7] ]. Considering 50 cases and 4 cases, most cases obtain platelets response using anti-tuberculosis treatment, corticosteroid and IVIG.…”
Section: Discussionmentioning
confidence: 99%
“…Time from treatment initiation until platelets recovery varies from some days to a few months. No severe fetal bleeding occurred in the clinical course [ 1 , [4] , [5] , [6] , [7] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation